Evaluasi Kebijakan Kota Layak Anak pada Pelayanan Ramah Anak di Puskesmas Kota Balikpapan - Sri Mulyati; Nuraisyah; Ani Susanti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research evaluates the policy of Child Friendly City (KLA) in child friendly services at Puskesmas Balikpapan City by using William N. Dunn's six policy evaluation criteria. The purpose of this study is to analyze and provide a deeper understanding of the evaluation of Child Friendly City policy on child friendly services at Puskesmas of Balikpapan City. Among 27 Puskesmas in Balikpapan City, this research will focus on six Puskesmas, namely Puskesmas Karang Joang, Manggar, Margo Mulyo, Klandasan Ilir, Sepinggan, and Mekar Sari. This study adopts a qualitative approach by using evaluative qualitative methods. The evaluation was conducted using 15 indicators of PRAP set by the Ministry of Women's Empowerment and Child Protection (KemenPPPA). The results showed that this policy was well implemented, but there were constraints on facilities and human resources at several health centers, especially at Puskesmas Margo Mulyo and Manggar. Evaluation based on Dunn's theory shows that effectiveness, efficiency, adequacy, and equity still need to be improved to fully achieve KLA goals.